Antropología corporativa y competitividad en la región Asia - Pacífico - Kikuchi, Yasushi (1999)
In this exhibition I will deal with corporate anthropology. Why do we link this topic to business activities in the Asia-Pacific region? Because anthropologists study cultural diversity. Culture is not one; Every ethnic group, every community, every country, every human group has its own different characteristics. And we must be able to appreciate the differences between one and the other, otherwise the only way to resolve them is by fighting, as in Kosovo.